Advance in Molecularly Imprinted Polymers (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The "Advance in Molecularly Imprinted Polymers" Special Issue establishes a connection between original research papers and reviews that showcase recent progress in the formulation, creation, and wide-ranging utilization of molecularly imprinted polymers. The content within this Special Issue encompasses a range of subjects pertaining to the chemistry of MIPs, encompassing aspects such as molecular modeling, the utilization of novel monomers and innovative synthesis methods for crafting MIPs, the synthesis and application of ion-imprinted materials, the selective extraction of organic compounds, the preparation of sensors, and the implementation of MIPs in the field of medicine. The compilation of scientific papers presented in this collection demonstrates the diverse landscape of research within MIPs chemistry, ultimately leading to the enhancement of desired traits and the exploration of fresh potential applications for these materials.